Policy evaluation by the synthetic control approach: The case of the Swiss franc - Nicole Aregger; Jessica Leutert (Swiss National Bank, Study Center Gerzensee, 2017)
In this paper, we analyse the effect of unconventional monetary policies on the EUR/CHF exchange rate. We apply the synthetic control approach to four events defining a change in the Swiss National Bank's monetary policy during the 2009 to 2011 period before the introduction of the exchange rate floor. We provide evidence that in some periods the EUR/CHF exchange rate shares common factors not only with other exchange rates, but in particular with other safe assets. It is thus possible to construct a counterfactual exchange rate by assigning weights to other exchange rates or safe assets. The synthetic control approach finds major effects for the March 2009 and August 2011 announcements. The methodology seems less appropriate to evaluate the spring 2010 foreign exchange interventions.
Keywords: E58; F31; G14; 330; Synthetic Control Approach; Foreign Exchange Interventions; Swiss Franc